Relationship between electrical impedance and physiological characteristics of wheat leaves in salt stress - LIU Xiao-hong; HUANG Ting-lin; WANG Guo-dong; ZHANG Gang (浙江大学学报. 农业与生命科学版)
A solution culture experiment was conducted to determine resistance and reactance of wheat leaves under NaCl stress, and the correlation between electrical impedance and physiological parameters such as protective enzyme (CAT, POD) activity, malondialdehyde (MDA), relative conductivity, moisture content and soluble sugar content was analyzed. The results show that, with increasing NaCl concentrations, extracellular resistance and relaxation time of wheat leaves increased first and then decreased, whereas intracellular resistance and distribution coefficient of relaxation time of wheat leaves decreased first and then increased. Catalase (CAT), peroxidase (POD), moisture content and soluble sugar content reduced, while MDA and relative conductivity increased with increasing NaCl concentrations. Extracellular resistance had significantly positive correlation with relaxation time. Except CAT, other physiological parameters were correlated significantly with extracellular resistance and relaxation time. Extracellular resistance and relaxation time of wheat leaves reflected approximately the variations of physiological properties in cell, thus they could assess the degree of salt stress for wheat.